THE INFLUENCE OF ISLAMIC EDUCATION MANAGEMENT ON STUDENT CHARACTER DEVELOPMENT - Loso Judijanto; Rusiadi (Adisam Publisher, 2025)
Islamic Education Management is a process of planning, organising, directing, and supervising in educational institutions based on Islamic values and teachings. The aim is to create an effective and efficient learning environment, as well as forming students who are not only superior in science and skills, but also have character and morals in accordance with Islamic teachings. This management covers various aspects of education, including curriculum, teaching methods, human resource development, infrastructure, and community relations, all of which are integrated with Islamic principles to achieve holistic and spiritually valuable educational goals. The research method used is a literature study. The results show that Islamic education management has an influence on student character development, which can be seen in four main aspects: (1) the integration of Islamic values in the curriculum and learning, (2) the development of teacher and staff competencies oriented towards Islamic character, (3) the management of facilities and infrastructure that support character building, and (4) the creation of an Islamic school environment. This study concludes that the implementation of effective Islamic education management can substantially improve the character building of students who are noble and ready to face global challenges while adhering to Islamic values.